KAJIAN PERMEABILITAS KAWASAN BUKIT BINTANG, MALAYSIA - Ari Widyati Purwantiasning; Saeful Bahri; Ahmad Rivai Fachrudin; ghifary ghifary (Universitas Muhammadiyah Jakarta, 2026)
This study aims to analyze the concept of permeability in the Bukit Bintang area, Malaysia, by relating it to the principles of community architecture. The main focus of this study is on the interaction between building blocks, circulation, and lane width, as well as how these elements contribute to social interaction and mobility in the area. Regional permeability is essential in creating an environment that supports interconnectedness between individuals and communities. The methodology used includes field observation, circulation mapping, and spatial analysis to evaluate the dynamics of movement in Bukit Bintang. The results show that building block designs that take into account community architectural principles, such as connectivity and accessibility, can improve user experience and encourage social interaction. Ample width and open public spaces contribute to the creation of an inclusive environment, where individuals can interact more freely. These findings emphasize the importance of designing that takes into account the needs of the community to create efficient and user-friendly public spaces. The recommendations of the study include improved connectivity between building blocks and the development of wider pedestrian paths, as well as the provision of open space that supports community activities. This research is expected to contribute to the design of a city that is more responsive to the needs of the community, as well as support the sustainable development of the area and strengthen social relations in Bukit Bintang.